The Efficiency Performance of CNC Milling Machine with Vibration Sensor - BINTI MOHD ZAKIR, AUNI ZAKIRAH; PROF. Ir. Dr. YUSRI BIN YUSOF (Research Progress in Mechanical and Manufacturing Engineering, 2026)
For the purpose of to determine the operational effectiveness and surface finish quality of a CNC milling machine fitted with a vibration sensor, this study analyses its performance. The variations in machine behaviour under various cutting parameters have been studied by integrating a real-time vibration monitoring system in order to identify the factors that result in excessive tool wear, chatter, and surface roughness. Early identification of inefficiencies and possible faults was made possible by the vibration sensor’s data, which offered useful details about the dynamic stability of the milling process. The findings show that vibration analysis is a dependable technique for improving cutting conditions, process control, and the overall precision and productivity of CNC milling operations.